Cervical muscle strength measurement in two groups of elite Greco-Roman and free style wrestlers and a group of non-athletic subjects - Rezasoltani, A.; Ahmadi, A.; Nehzate-Khoshrosh, M.; Forohideh, F.; Ylinen, J. (British Journal of Sports Medicine, 2005)
Objectives: The aim of this study was to examine the maximal isometric strength of cervical extension (ISCE) and the maximal isometric strength of cervical flexion (ISCF) in two groups of elite wrestlers and a group of non-athletic subjects.